CDKL5 mutations cause infantile spasms, early onset seizures, and severe mental retardation in female patients. Issue 9 (12th April 2006) - Archer, H L; Evans, J; Edwards, S; Colley, J; Newbury-Ecob, R; O'Callaghan, F; Huyton, M; O'Regan, M; Tolmie, J; Sampson, J; Clarke, A; Osborne, J
Abstract : Objective: To determine the frequency of mutations in CDKL5 in both male and female patients with infantile spasms or early onset epilepsy of unknown cause, and to consider whether the breadth of the reported phenotype would be extended by studying a different patient group. Methods: Two groups of patients were investigated for CDKL5 mutations. Group 1 comprised 73 patients (57 female, 16 male) referred to Cardiff for CDKL5 analysis, of whom 49 (42 female, 7 male) had epileptic seizure onset in the first six months of life. Group 2 comprised 26 patients (11 female, 15 male) with infantile spasms previously recruited to a clinical trial, the UK Infantile Spasms Study. Where a likely pathogenic mutation was identified, further clinical data were reviewed. Results: Seven likely pathogenic mutations were found among female patients from group 1 with epileptic seizure onset in the first six months of life, accounting for seven of the 42 in this group (17%). No mutations other than the already published mutation were found in female patients from group 2, or in any male patient from either study group. All patients with mutations had early signs of developmental delay and most had made little developmental progress. Further clinical information was available for six patients: autistic features and tactile hypersensitivity were common but only one had suggestive Rett-like features. All had a severe epileptic seizure disorder, all but one of whom had myoclonic jerks. The EEG showed focal or generalised changes and in those with infantile spasms, hypsarrhythmia. Slow frequencies were seen frequently with a frontal or fronto-temporal predominance and high amplitudes. Conclusions: The spectrum of the epileptic seizure disorder, and associated EEG changes, in those with CDKL5 mutations is broader than previously reported. CDKL5 mutations are a significant cause of infantile spasms and early epileptic seizures in female patients, and of a later intractable seizure disorder, irrespective of whether they have suspected Rett syndrome. Analysis should be considered in these patients in the clinical setting.